2019
DOI: 10.1167/19.7.9
|View full text |Cite
|
Sign up to set email alerts
|

Development of spatial suppression surrounding the focus of visual attention

Abstract: In adulthood, research has demonstrated that surrounding the spatial location of attentional focus is a suppressive field, resulting from top-down attention promoting the processing of relevant stimuli and inhibiting surrounding distractors (e.g., Hopf et al., 2006). It is not fully known, however, how this phenomenon manifests during development. This is an important question since attention processes are likely even more critical in development because of their potential impact on learning and day-today acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
(133 reference statements)
1
0
0
Order By: Relevance
“…Full visual function is not available until late adolescence. We have looked at a specific attentional function, the attentive suppressive surround, and confirmed such a late development (Wong-Kee-You et al 2019). We found that this suppression is not seen in children at all until about 7-8 years old and only matures by 17-18 years old.…”
Section: A Sketch Of An Active Attention Controllersupporting
confidence: 59%
“…Full visual function is not available until late adolescence. We have looked at a specific attentional function, the attentive suppressive surround, and confirmed such a late development (Wong-Kee-You et al 2019). We found that this suppression is not seen in children at all until about 7-8 years old and only matures by 17-18 years old.…”
Section: A Sketch Of An Active Attention Controllersupporting
confidence: 59%